Iron status among blood donors deferred due to low haemoglobin level - Kovač, Mirjana; Erić, Bojana; Stojneva Istatkov, Jelena; Lukić, Vojislav; Milić, Ana; Vukičević, Dragana; Orlić, Dušan; Tomić, Branko (Vojnosanitetski pregled, 2021)
Background/Aim. Haemoglobin (Hb) determination is a routine part of the blood donor selection process. Previously reported studies have revealed that iron deficiency is common in frequent donors. This prospective investigation was aimed at examining iron status among blood donors with low circulating Hb and evaluating correlation between Hb values determined by capillary methods and those obtained by reference method from venous blood count (BC), as well as ferritin level. Methods. Between February 2017 and December 2018, 200 consecutively recruited regular blood donors with low Hb, aged 19 to 64 years (median 39), were included. Hb level was determined using the copper sulphate method, the HemoCue capillary method, and also from venous blood within the complete blood count (CBC) test. Plasma ferritin was determined turbidimetrically. Results. In 42.7% of men and 57.3% of women, ferritin concentration was low (p = 0.008). The relative numbers of males and females, with levels < 12 μg/L (p = 0.023) or > 50 μg/L (p = 0.022), differed. Comparison of the values obtained with the capillary methods with reference Hb levels obtained from the CBC test showed that the copper sulphate procedure gave false fails in 10.5% of cases (p < 0.001). Hb values from HemoCue were significantly correlated with Hb values from the CBC test, but no correlation was observed between ferritin levels and Hb levels determined by both capillary method. Conclusion. Low ferritin was observed in 51.5% of Serbian blood donors deferred due to low Hb. Based on our results, the determination of the algorithm in the iron deficiency detection is necessary, while the capillary method (HemoCue) represents a more convenient method for Hb testing prior to blood donation.